Live Survival Strategy to Grow Entrepreneurial Interest in the Perspective of Maqashid Asy-Syari'ah (On Deaf-Mute Disabilities UPT RSBRW - Pasuruan) - Azizah, Lailatul (Universitas Airlangga, 2024)
Difficulties for people with hearing and speech impairments in accessing formal employment because companies only open and look for workers in the physically & mentally healthy category, to increase productivity & effectiveness of employee performance. While getting a job is very important & fundamental for sustainability & continuity. One of the problems faced by people with hearing impairments is how to develop skills & knowledge according to their talents and interests, so that they are able to move independently in fulfilling and prospering their needs & desires without depending on the informal sector.This research is descriptive research with a qualitative approach. The researcher will describe survival strategies to foster interest in entrepreneurship for people with hearing and speech impairments according to field conditions with the aim of finding a comprehensive survival strategy formulation. From the results of data analysis in the field, it is clear that the concept of success in the presence of limitations / impairments is that there are 3 types of survival strategies used by people with hearing and speech impairments, namely: active strategy (having, independence, confidence, enthusiasm, optimism, perseverance), passive strategy (making savings in meeting needs: dharuriyat, hajiyat, tahsiniyat, and implementing rational consumption patterns/ mustahlik al-aqlani), network strategy (using available accessibility & building relationships with related agencies).